Impact of a Mediating Role of Repurchase Intentions on Customer Retention - Milan Ambrož; Branko Lotrič (Promet - Traffic&Transportation, 2012)
Research in the area of packaged tour services, provided by the national and foreign tour operators has concentrated on mutual relationships among tourist-perceived service quality, satisfaction and repurchase intentions. However, little research in this domain has been done to explain the impact of repurchase intentions of experienced tourists on the relation between perceived quality of service and their satisfaction. This model was tested using substantial data set of experienced tourists with time span of three years. While previous literature has suggested that quality perceptions impose direct effect on tourist satisfaction, this study shows that such effect is more powerful when mediated by repurchase intentions of experienced tourists. The quality of packaged tour services mediated by repurchase intentions of the experienced tourist is expected to be paramount for the retention of the tourist in the long term.KEY WORDS: repurchase intentions, quality, packaged service, services chain, tour operator, retention, tourist satisfaction.